Reconstruction of Radioscaphocapitate Ligament in Treatment of Ulnar Translation - Aita, Marcio Aurelio; Alves, Rafael Saleme; Ibanez, Daniel Schneider; Consoni, Daniel Alexandre Pereira; de Oliveira, Ricardo Kaempf; Ruggiero, Gustavo Mantovanni (Journal of Wrist Surgery, 2019)
Background This article measures the life quality, clinical, and functional outcomes of a patient who had undergone reconstruction of the radioscaphocapitate ligament (RSL), using brachioradialis tendon in the treatment of ulnar translation of the carpus.Case Description We present a 36-year-old man with ulnar translation in his left, nondominant wrist, after fall accident. Reconstruction of the RSL was performed. One year later, the patient experienced good evaluation. Wrist flexion was 70 degrees, extension was 60 degrees, radial deviation was 20 degrees, and ulnar deviation was 30 degrees. Forearm pronation was 85 degrees and supination was 90 degrees and digit motion was full. Disabilities of the Arm, Shoulder and Hand score of 5, Visual Analog Scale of 0, and grip strength of 82% were obtained compared with the unaffected side. Wrist radiographic aspects showed radiocarpal joint congruency. The period of fixator treatment was 8 weeks. Good stability and joint congruency of the radiocarpal joint were obtained. Good radiographic, clinical, and functional results were obtained improving the quality of life of the patient.Literature Review The treatment of ulnar translation is difficult and complicated. There is no consensus to the overall management. As there is still a lack of long-term results, the indications for surgery, various surgical options, and the type of intervention have been a matter of controversy in the literature. Would radiocarpal joint be stable when reconstruction of the RSL using brachioradialis tendon was obtained? Is it possible to reduce an ulnar translation with this technique?Clinical Relevance We would like to suggest that the radiocarpal ligament reconstruction will improve the outcome. We believe that this technique will make the wrist more stable and functional. We agree that the best time to perform the corrections is early. The authors prefer to first reconstruct the RSL and then the radiocarpal ligament suture or radioscapholunate arthrodesis.
Keywords: ulnar translation; forearm deformity; wrist deformity; ligament reconstruction; radiocarpal ligaments